Data-driven exploration of new pressure-induced superconductivity in PbBi2Te4. Issue 1 (31st December 2018) - Matsumoto, Ryo; Hou, Zhufeng; Nagao, Masanori; Adachi, Shintaro; Hara, Hiroshi; Tanaka, Hiromi; Nakamura, Kazuki; Murakami, Ryo; Yamamoto, Sayaka; Takeya, Hiroyuki; Irifune, Tetsuo; Terakura, Kiyoyuki; et al.
ABSTRACT: Candidate compounds for new thermoelectric and superconducting materials, which have narrow band gap and flat bands near band edges, were exhaustively searched by the high-throughput first-principles calculation from an inorganic materials database named AtomWork. We focused on PbBi2 Te4 which has the similar electronic band structure and the same crystal structure with those of a pressure-induced superconductor SnBi2 Se4 explored by the same data-driven approach. The PbBi2 Te4 was successfully synthesized as single crystals using a melt and slow cooling method. The core level X-ray photoelectron spectroscopy analysis revealed Pb 2+, Bi 3+ and Te 2- valence states in PbBi2 Te4 . The thermoelectric properties of the PbBi2 Te4 sample were measured at ambient pressure and the electrical resistance was also evaluated under high pressure using a diamond anvil cell with boron-doped diamond electrodes. The resistance decreased with increasing of the pressure, and pressure-induced superconducting transitions were discovered at 2.5 K under 10 GPa. The maximum superconducting transition temperature increased up to 8.4 K at 21.7 GPa. The data-driven approach shows promising power to accelerate the discovery of new thermoelectric and superconducting materials. GRAPHICAL ABSTRACT: